Clinical application of the modified posterolateral approach for treating posterior tibial plateau fractures - Shuaishuai, Wang; Minglei, Zhang; Yue, Yu; Dapeng, Wang; Tongtong, Zhu; Huimin, Liu (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: To investigate the therapeutic efficacy of the modified posterolateral approach on tibial plateau fractures. Methods: Forty-four patients with tibial plateau fractures were enrolled in the study and divided into two groups—control and observation—according to the different surgical procedures. The control group underwent fracture reduction via the conventional lateral approach, while the observation group underwent fracture reduction via the modified posterolateral strategy. The depth of tibial plateau collapse, active mobility, and the Hospital for Special Surgery (HSS) score and Lysholm score of the knee joint at 12 months after surgery were assessed in comparison to the two groups. Results: The amount of blood loss (P < 0.01), duration of surgery (P < 0.05), and depth of tibial plateau collapse (P < 0.001) were significantly less in the observation group compared with the control group. In addition, compared with the control group, the observation group exhibited significantly better knee flexion and extension function and significantly higher HSS and Lysholm scores at 12 months after surgery (P < 0.05). Conclusion: The modified posterolateral approach for posterior tibial plateau fractures has less intraoperative bleeding and a shorter operative time compared with the conventional lateral approach. It also effectively prevents postoperative tibial plateau joint surface loss and collapse, promotes the recovery of knee function, and has few postoperative complications and good clinical efficacy. Thus, the modified approach is worth promoting in clinical practice.